Influence of the positive Indian Ocean Dipole in 2012 and El Niño-southern oscillation (ENSO) in 2015 on The Indonesian Rainfall Variability. (May 2019) - Mareta, Lesi; Hidayat, Rahmat; Hidayati, Rini; Alsepan, Givo
Abstract: Indian Ocean Dipole (IOD) and El Niño-southern oscillation (ENSO) are coupled ocean – atmosphere variability in the Indo – Pacific Oceans that play important roles to the Indonesian rainfall variability. This study is focused on the influence of the positive IOD in 2012 and El Niño in 2015 on the rainfall in Indonesia using satellite-derived precipitation data. Sea surface temperature (SST), rainfall and wind components, are analyzed to evaluate the detailed evaluation of those events. The results show that, in 2012, the positive IOD develops in July - October and reaches its peak in September. During the positive IOD in 2012, there is a negative SST anomaly in the eastern Indian Ocean (western Sumatra). This causes a shift in the warm water pool to the western Indian Ocean. This shifted warm pool is accompanied by a shift in the convective region, leading to deareased rainfall in the western Sumatra. Mean while, in 2015, El-Niño started to develop from July to November. Negative anomalies of rainfall in the transition period II and the east monsoon season are in line with the SST elevation in the eastern and central Pacific Ocean. So that the eastern and central of the Pacific Ocean become to center of low pressure which causes the air in the eastern Pacific Ocean to upward (convection) which will form a clouds that contain water, so that the eastern and central of the Pacific Ocean will experience an increase in the amount of rainfall while in the western of the Pacific Ocean or the eastern of Indonesia will experience a rainfall deficit.